Potential Of Butterfly Pea Flower (Clitoria Ternatea) Extract As An Antidiabetic Agent: Literature Review - Lestari, Puput Legia; Ariyanto, Muhammad Wahyu; Nadhiroh, Wafda Safanah; Sulastri, Afianti; Somantri, Budi; Amalia, Linda (STIKes Ibnu Sina Ajibarang, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia due to insulin deficiency or insulin resistance. The global prevalence of diabetes mellitus continues to increase, posing a significant health and economic burden to society. Conventional pharmacological treatments that are currently available often cause unwanted side effects, so alternative therapies that are safer and more effective are needed. This study aims to collect and analyze data related to the effectiveness of flower extract as an antidiabetic agent in reducing blood glucose levels and preventing complications associated with diabetes. The potential of Clitoria ternatea as an antidiabetic agent was explored through a systematic literature review. Article searches were conducted using scientific databases such as Google Scholar, ScienceDirect, and Mendeley with the keywords